2004
DOI: 10.1021/np049811x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Phloroglucinols and Terpenoids from Garcinia subelliptica

Abstract: Three new phloroglucinols, garcinielliptones K (1), L (2), and M (3), and two new terpenoids, garcinielliptones N (4) and O (5), have been isolated from the seeds of Garcinia subelliptica. The structures of 1-5 including their relative configurations were elucidated by spectroscopic methods and supported by computer-generated molecular modeling. Compounds 2 and 3 showed potent inhibitory effects on the release of beta-glucuronidase, and on beta-glucuronidase and histamine, respectively, from peritoneal mast ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 9 publications
2
57
0
Order By: Relevance
“…Garcinia species have been reported to contain phloroglucinols (garcinielliptones A, B, C, D, F, H, I, K, L & M), terpenoids (garcinielliptone E, G, J, N & O), xanthones (mangostins), and their derivatives, and some have been shown to possess anti-inflammatory effects (Gopalakrishnan et al, 1980;Shankaranarayan et al, 1979;Weng et al, 2003aWeng et al, , 2003bWeng et al, , 2004. The pericarp of G. mangostana containing high levels of xanthones has been shown to be highly effective in scavenging free radicals and suppressing the production of pro-inflammatory cytokines (Chomnawang et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Garcinia species have been reported to contain phloroglucinols (garcinielliptones A, B, C, D, F, H, I, K, L & M), terpenoids (garcinielliptone E, G, J, N & O), xanthones (mangostins), and their derivatives, and some have been shown to possess anti-inflammatory effects (Gopalakrishnan et al, 1980;Shankaranarayan et al, 1979;Weng et al, 2003aWeng et al, , 2003bWeng et al, , 2004. The pericarp of G. mangostana containing high levels of xanthones has been shown to be highly effective in scavenging free radicals and suppressing the production of pro-inflammatory cytokines (Chomnawang et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Garsubellin A exhibited the antiinflammatory property by the inhibition of release of b-glucuronidase and histamine. The compound found to be more potent than the reference standard mepacrine (Weng et al 2003(Weng et al , 2004. These results suggested that phloroglucinols could be very effective in treating inflammation and neurodegenerative diseases.…”
Section: Miselenious Compoundsmentioning
confidence: 98%
“…[8] There is a great number of researchers dealing with compounds extracted from Garcinia species concerning biological properties, and the anti-inflammatory potentials of such substances are already known, which contribute to the antiphlogistic activity of resins from Garcinia species and explain the rational use of these plants in folk medicine. [9,10] Polyprenylated benzophenones are substances biologically active from Guttiferae family. Some of them were isolated from Symphonia globulifera, Garcinia livingstonei, Garcinia ovalifolia and Clusia rosea as HIV-inhibitory compounds.…”
Section: Introductionmentioning
confidence: 99%